Formulation of Flavor Enhancer from Shiitake Mushroom (Lentinula edodes) with the Addition of Mackerel Fish (Scomberomorus commerson) and Dregs Tofu Hydrolysates (Indonesian Journal of Chemical Science, 2022)
A flavor enhancer is a food additive that can give a certain taste. Synthetic/artificial flavor enhancers are currently widely used in public, but excessive use can have an impact on health problems, so they can be replaced by using natural flavor enhancers. This study aims to make natural flavorings with the basic ingredients of shiitake mushrooms, mackerel fish hydrolyzate, and tofu dregs hydrolyzate. The method used in this study was a Completely Randomized Design. The flavoring was done by varying the composition into 3 formulas with successive ratios of shiitake mushrooms, mackerel fish hydrolysate, and tofu dregs hydrolysate are 1:2:2, 2:1:2, and 2:2:1 which were then analyzed using the Kruskal Wallis and continued with the Mann-Whitney test and analyzed using the Exponential Comparison Method to determine the best formula. The results showed that formula 3, namely flavoring with a composition ratio of 2:2:1, was the chosen formula based on the assessment in organoleptic tests. The flavoring of formula 3 was then carried out with a proximate test and the results obtained were 10.1% water content, 6.5% ash content, 26.4% protein content, 19.9% ​​fat content, and 18.5% fiber content. Based on the research, it can be seen that the flavoring of shiitake mushrooms with the addition of hydrolyzate of mackerel fish and tofu dregs can be used as a substitute for synthetic flavoring and has good nutritional content.